Economic Crisis in a Context of Marital Crises: the Courts in the Context of New Family Models - Muñoz Catalán, Elisa (DIXI, 2015)
Introduction: Starting with approval of the Spanish Civil Code in the 19th century, Spain has experienced signifiant and numerous legal and social transformations. Thse have not only affcted family law in general but also, and particularly, the regulation of marriage and the new family models in terms of their consequences in situations of marital crisis.Methodology: In that sense, this research article looks at existing legislative innovations in the fild, introduced in recent decades, with the aim of examining the scope of diffrent rulings that effctively show how the civil courts, faced with a situation of widespread economic crisis, try to adapt to the new social reality and award an essential role to grandparents in processes of nullifiation, separation or divorce.Conclusions: It also analyzes how in exceptional situations, for example in the recent ruling of March 2, 2015, separated parents who are unemployed and live in persistent poverty are permitted to stop paying child support without even paying the so-called “ vital minimum” until they are able to obtain the necessary funds for subsistence.
Keywords: crisis; family; marriage; minors; pension; courts